'Mafia Capitale': judicial and symbolic constructions of the new Italian corruption. Issue 3 (27th May 2019) - Pezzi, Maria Giulia
ABSTRACT: The article looks at the case of Mafia Capitale, a criminal organization recently operating in Rome which aimed at controlling the allocation of public funds in the private sector through bribery and other illicit practices such as extortion, violence and corruption in general. It will be maintained that Mafia Capitale has challenged the understanding of the possible intersections between organized crime and corruption practices, constituting a turning point in the way how both crimes are symbolized, represented, constructed and prosecuted. The article provides an analysis of the judicial instruments used to define mafia-like criminal organizations in Italy, confronted with their symbolic construction, as emerging from investigations and wiretappings. The final goal is to discuss whether judicial texts can be used as secondary data for ethnographies of crime and corruption.